The Pecularities of Academic Youth’s Professional Vocation and Its Development - Jurevičiūtė, Kristina (Acta Paedagogica Vilnensia, 2004)
The purpose of this research was to reveal the peculiarities of students’ professional vocation and the change of its importance through youth's vocational development entering the university. While trying to achieve this objective, firstly, the concept of professional vocation was analysed to define the relation of the notions of professional fitness and professional purposefulness with the notion of vocation. Moreover, the investigation of professional vocation's motivational, potential and character spheres and their elements was made. Therefore, the theoretical model of professional vocation was created. Moreover, it was compared to the outcome of the statistical research model, thus new psychological formations of professional vocation were framed. The data of research revealing the peculiarities of students' professional vocation was compared accordingly to students' professional choice in high school with the imaginative choice of profession during the studies at university.
Keywords: academic youth; professional vocation; motivation; choice of profession